Hubungan Kadar Kolesterol Total Dengan Kolesterol LDL Pada Pasien Hipertensi - So Hanggrainy, Octavia; Lim, Hadyanto; Singh, Surjit (Universitas Methodist Indonesia, 2024)
The Background: Cholesterol is an essential structural component that forms the cell membrane and the external layer of plasma lipoproteins. The increase of total cholesterol is always accompanied by the increase in LDL cholesterol especially in hypertensive patients. The present study was conducted to find the correlation between total cholesterol and LDL cholesterol of the patients with hypertension Method: It is an observational analytic using cross sectional study in which the data were collected by clinical laboratory examination of Prodia Jl. S.Parman no. 17/223G Medan, North Sumatra Indonesia. The population included all patients with hypertension in which the samples were taken by consecutive sampling method so the total were 19 samples. Results: Majority of samples had normal total cholesterol of 8 persons (42.1%) and the majority of the study samples had high LDL cholesterol of 8 persons (42.1%). Conclusion: There is a significant correlation between total cholesterol and LDL cholesterol. It is indicated by the sig-p value = 0.004 (p <0.05). There is a significant correlation between total cholesterol and LDL cholesterol of the patients with hypertension. It is indicated by the correlation coefficient value r-count = 0.635 which is between 0.6 - 0.79